Strategi Pembelajaran Non Directive pada Mata Pelajaran Akidah Akhlak di MTs S TI Paraman Ampalu - Najmi, Hayatun; Nurdin, Syafruddin; Marhamah (At-Tadris: Journal of Islamic Education, 2023)
Non-Directive learning strategies are learning strategies that direct students to be more active and think critically in learning. Emphasizes efforts to facilitate learning, achieve personal integration and maximize students' thinking power by providing support for the spirit of religious learning. Students are trained to think across disciplines, solve every problem according to their abilities and desires and must be accountable. This way students have more space. to be creative and increase the spirit of learning. The role of the teacher as a facilitator. The research method used is descriptive qualitative research and the technique used uses interview techniques. Qualitative descriptive research produces information in the form of quality and reliable data whose authenticity can be accounted for. It can be concluded that one of the benefits of discovery learning is helping students develop their critical thinking skills. Another benefit is encouraging students' interest and curiosity in creating alternatives and solving problems as well as encouraging creativity and the development of better interpersonal skills and abilities if teachers can effectively explain how to manage, and directing students, then existing deficiencies can be corrected. Non-directive learning, the teacher only provides the main points of the assignment, which have been arranged so that with this assignment, students can carry out observations on the lesson object, analyze the facts encountered, draw conclusions about the results of their own observations, explain what has been found and compare it with other facts. Therefore, to use this non-directive learning technique successfully and efficiently, teachers must first understand the basic principles